Microwave assisted extraction (MAE) of beta-sitosterol from plant legumes pod - Norlaili, Hashim (2019)
Archidendron pauciflorum or Jering, Petai or Parkia speciosa, and Leucaena leucocephala or Petai Belalang are all known as a local delicacy to many countries in Asia and yet also have the beneficial aspect in health such as an antimicrobial, antioxidant, hypoglycaemic, antiulcer and anti-hypertension. Present studies only shows on the present of phytosteroid in the plant but not its concentration. The extraction process of beta-sitosterol performed by using Microwave-Assisted Extraction process. After the extraction process, the characterization process was done by using ultraviolet-visible spectroscopy (UV-VIS), Fourier transform infrared (FTIR), high-performance liquid chromatographic analysis (HPLC) and scanning electron microscope (SEM). UV-Vis analysis analyse concentration of beta-sitosterol content in the legume pod while the FTIR will give the functional group of the legume pod. SEM shows the condition of plant surface before and after the extraction process and to ensure the extraction process at desired parameter condition. In order to optimize the maximum yield extraction of beta-sitosterol, the extraction parameter was optimize by using response surface method (RSM) by using Design Expert 7.0. The optimization process was done by using one factor at a time (OFAT) for the screening process where the research will be continued with legume pod that content with the highest yield of beta-sitosterol, fractional factorial design (FFD) for screening extraction process parameter and central composite design (CCD) for the optimization of the extraction process will be required in order to plan and investigate the most required processes. OFAT process was done by using four parameters, which are extraction duration, irradiation power, solvent concentration and extraction temperature with all three types of plant. From OFAT study result, FFD was continued with time and solvent concentration with only L. leucocephala legume. CCD result was optimized with 62.5% ethanol solvent, 7.45 min of extraction duration, 600W irradiation power and 75ºC irradiation temperature to give the highest yield of beta-sitosterol which is 0.31 mg/mL.